Acrometastasis as a first sign of lung cancer - Tomić, Miroslav; Jovanović, Mladen; Tomić, Mirjana; Živojinov, Mirjana (Vojnosanitetski pregled, 2024)
Introduction. Bone metastases occurring distally to the elbow or knee joint are called acrometastases. Acrometastases make up only 0.1% of all bone metastases, but only 0.007% to 0.3% occur in the bones of the foot or hand. In 10% of patients, bone metastases occur as the first sign of a previously undiagnosed primary tumor. Case report. A 64-year-old male reported to the hospital due to painful swelling and redness of the fifth finger of the dominant hand. Osteolysis of the proximal phalanx of the fifth finger was diagnosed radiographically. A working diagnosis of osteomyelitis and phlegmon of the proximal phalanx was made. After incisional drainage, a tumor mass was observed intraoperatively. Amputation of the finger was performed at the level of the metacarpophalangeal joint. Pathohistological analysis revealed squamous cell carcinoma metastasis. After a computed tomography scan and bronchoscopy with biopsy, a diagnosis of squamous cell carcinoma of the bronchus was made. The patient was given chemotherapy. During the application of the second cycle, there was a fatal outcome. Conclusion. Pathohistological verification and determination of the location of the primary tumor are important when acrometastasis is found because starting novel immunotherapy and targeted therapy in a timely manner could change the median survival of these patients.